Antecedents of Environmental Management Accounting and Environmental Performance: Evidence from Indonesian Small and Medium Enterprises - Susanto, Azhar; Meiryani, Meiryani (International Journal of Energy Economics and Policy, 2019)
Small and Medium Enterprises (SMEs) play a significant role in Indonesian business growth. Therefore, the objective of the present study is to investigate the association of antecedents of environmental management accounting and environmental performance in Indonesian SMEs. In doing so, the current study seeks to identify the internal and external influencing factors for firms in adopting EMA and its subsequent impact on SMEs environmental performance. the outcomes of the PLS-SEM confirm that Benefit Expectation has significantly and positively impacted on Environmental Management Accounting. The results of PLS-SEM also confirm that Regulatory Pressure has a positive and significant impact on Environmental Management Accounting. Finally, the results of partial least square modelling confirm that Environmental Management Accounting also has a positive and significant impact on Environmental Performance. Keywords: Environmental management accounting, environmental performance, SMEs, Indonesia. JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8366